(untitled) (Revista de Investigaciones Universidad del Quindío, 2020)
The main purpose of this article is to demonstrate that the municipality sphere represents the basis of Mexican federalism and, therefore, should be normatively included as such in the Mexican constitution. To verify this, it was necessary to conduct a qualitative study regard the current regulations under hermeneutics applied to the sources of law (formal, real and historical) in relation to this subject, as part of the method of legal sciences. The main result obtained was that it is necessary to amend the Mexican constitution to include the municipal sphere within the federal union. This would be congruent with the context in which Mexican federalism emerged as the municipality (territorial organization) and its council (government structure) are entities prior to the subsequent transition from the Spanish provinces to the current states and its integration into a federation after the Mexican Independence.